2020
DOI: 10.3390/en13236328
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Evaluation on the Influence of Washing Methods for Biodiesel Produced from High Free Fatty Acid Waste Vegetable Oils through Selected Quality Parameters

Abstract: The increasing use of alternative energy sources has brought benefits like the recycling of waste vegetable oils (WVO) for biodiesel production; however, this practice presents challenges derived from a highly variable raw matter. Our research focused on the washing techniques usually employed by small to medium scale producers which may lack the infrastructure to perform high-grade purification and often relay on the employment of “artisanal” technology. We report biodiesel production from pure canola oil (C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…From the study conducted by Sandouqa et al 52 . and Ortiz‐Lechuga et al 57 . using the same type of feedstock, the yields of purification differed from one another.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the study conducted by Sandouqa et al 52 . and Ortiz‐Lechuga et al 57 . using the same type of feedstock, the yields of purification differed from one another.…”
Section: Resultsmentioning
confidence: 99%
“…56 In comparison with other studies, as shown in Table 3, the purification yields of biodiesel varied depending on the feedstock used and the bio-based adsorbent used. From the study conducted by Sandouqa et al 52 and Ortiz-Lechuga et al 57 using the same type of feedstock, the yields of purification differed from one another. This demonstrated that bio-based adsorbent from delignified olive cake had better adsorption in reducing the acid value of biodiesel as compared with sawdust.…”
Section: Residence Timementioning
confidence: 99%
“…Free fatty acid is produced from the hydrolysis reaction between fatty acid methyl esters and water, increasing biodiesel's acid value [29]. Water in the hydrolysis reaction divides the reacted compound into two parts.…”
Section: Acid Valuementioning
confidence: 99%